2015
DOI: 10.1021/es5050375
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Little Brown Bat (Myotis lucifugus) Maternity Colonies and Its Correlation with Freshwater Acidity in Nova Scotia, Canada

Abstract: Insectivorous little brown bats are exposed to elevated concentrations of mercury (Hg) through their preference for aquatic-based prey. Here we investigated spatial patterns of total Hg (THg) in fur from 10 little brown bat maternity colonies across Nova Scotia, and assessed relationships with the acidity of nearby lakes and rivers. Total Hg concentrations were measured in fur samples from 149 adult female little brown bats. Values showed significant variation among colonies (mean range 3.76-27.38 μg/g, dry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The concentrations of Hg in fur observed in the present study all fell within the previously reported ranges for their respective species, although the bats collected in the present study often had lower maximum values than have been reported previously . For a given species, we may have observed lower maximum values in the present study because none of our study sites are located near point sources, as was the case in previous studies .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The concentrations of Hg in fur observed in the present study all fell within the previously reported ranges for their respective species, although the bats collected in the present study often had lower maximum values than have been reported previously . For a given species, we may have observed lower maximum values in the present study because none of our study sites are located near point sources, as was the case in previous studies .…”
Section: Discussionsupporting
confidence: 86%
“…The concentrations of Hg in fur reflect the Hg concentrations in bat diets at the time that the hair was grown, usually during late summer/early autumn before migration begins . The concentration of Hg in fur can also be influenced by local point sources of contamination and has even been shown to vary in resident bats at sites relatively close to one another (e.g., between sites in Nova Scotia ). In the present study, the concentration of Hg in the fur of migrant bats likely reflects the Hg contamination at sites across the central United States, and the presence of migrants from a few Hg hotspots could explain the wide range of Hg concentration values we observed within a single species in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidneys, therefore, represent a valuable indicator for exposure of bats to non-essential metals (Cooke, 2011;Ma, 2011). Fur can represent a valuable less-invasive proxy for endogenous metals contamination monitoring (Hernout et al, 2016;Little et al, 2015), although cautious interpretation is during the time of formation of the fur. Therefore, the moulting cycle is an important factor to consider (Fraser et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies are lacking on a larger scale. A recent study has shown associations between freshwater acidity and mercury concentrations contained in bat fur (Little et al, 2015), and such studies on a larger scale are therefore to be encouraged.…”
Section: Discussionmentioning
confidence: 99%